Oxygen abundance maps of CALIFA galaxies - Zinchenko, Igor A.; Pilyugin, Leonid S.; Grebel, Eva K. (Arxiv, 2016)
We construct maps of the oxygen abundance distribution across the disks of 88 galaxies using CALIFA data release 2 (DR2) spectra. The position of the center of a galaxy (coordinates on the plate) were also taken from the CALIFA DR2. The galaxy inclination, the position angle of the major axis, and the optical radius were determined from the analysis of the surface brightnesses in the SDSS